Women and Crime - Ghosh, Srikanta, 1913- (New Delhi : Ashish Pub. House, 1993)
Survey of crimes commited by women, against women, and for women in India.
Includes bibliographical references and index.
Keywords: Women -- Crimes against -- India; Female offenders -- India; Criminal statistics -- India